Stimulation of complement production in mice by N alpha-(N-acetylmuramyl-L-alanyl-D-isoglutamine)-N epsilon-stearoyl-L-lysine. - Endo, N (1983)
N alpha-(N-acetylmuramyl-L-alanyl-D-isoglutamine)-N epsilon-stearoyl-L-lysine, a synthetic muramyl dipeptide analog, stimulated the production of the third component of complement (C3) in mice. The serum concentration of C3 was elevated significantly by subcutaneous treatment with a single dose (10 to 100 micrograms per mouse) of the adjuvant 24 h before assay of the serum. Thereafter, the concentration decreased gradually with time and returned to the normal level on day 4 to 5. Immunoelectrophoretic analysis of the serum revealed that the decrease in serum C3 could not be accounted for by the cleavage to C3a and C3b. By intermittent treatment with the adjuvant on every fifth day, a significant increase in serum C3 was repeated. However, no continuous retention of the serum level of C3 was established even during continuous treatment with the adjuvant once a day for 10 consecutive days. Instead, in this case, the level of C3 increased repeatedly at almost 5-day intervals.